Sexual partner characteristics and incident rectal Neisseria gonorrhoeae and Chlamydia trachomatis infections among gay men and other men who have sex with men (MSM): a prospective cohort in Abuja and Lagos, Nigeria. (24th February 2017) - Ramadhani, Habib O; Liu, Hongjie; Nowak, Rebecca G; Crowell, Trevor A; Ndomb, Teclaire; Gaydos, Charlotte; Peel, Sheila; Ndembi, Nicaise; Baral, Stefan D; Ake, Julie; Charurat, Man E
Abstract : Background: STIs including Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) potentiate HIV acquisition and transmission especially among gay men and other men who have sex with men (MSM). We investigated the influence of sexual network composition on incident rectal NG and/or CT infections among Nigerian MSM. Methods: TRUST/RV368 is a cohort of MSM recruited using respondent-driven sampling at trusted community centres in Abuja and Lagos, Nigeria. MSM respondents (egos) provided STI risk factors and demographic information for up to five of their most recent sexual partners (alters) within their sexual networks. Egos were tested for HIV, NG and CT every 3 months. Log-binomial regression was used to assess associations between alter characteristics and incident NG and/or CT. Results: Between March 2013 and October 2015, 492 MSM were longitudinally screened for STIs, of which 28.0% (n=138) were positive for incident rectal STI (61 NG only, 42 CT only and 35 NG and CT). Among egos, condom use was associated with STIs (half of the time vs never (adjusted risk ratio (aRR) 0.5; 95% CI 0.3 to 0.8), always/almost always vs never (aRR 0.7; 95% CI 0.5 to 1.0)). Incident STIs were associated with having a younger alter ≤19 versus 30 years (aRR 0.6; 95% CI 0.4 to 1.0), HIV infection (aRR 1.5; 95% CI 1.1 to 2.0) and engaging in sex under the influence of alcohol (aRR 1.4 95% CI 1.1 to 1.7) among regular alters and age ≤19 versus 30 years (aRR 0.3; 95% CI 0.2 to 0.6), HIV infection (aRR 1.4; 95% CI 1.1 to 1.8) and engaging in sex under the influence of alcohol (aRR 1.2 95% CI 1.0 to 1.4) among casual alters. Conclusions: Given the centrality of sexual partner characteristics as risks for incident STIs among Nigerian MSM, there is a need to move beyond individual interventions and syndromic surveillance and get 'out there' in the STI management.